Study of the verb type in the poetic group: (If I had a thousand pens) by the poet Jaleh Esfahani - Obaid, Mustafa Ali; Muhammad, Aqeel Abdul Hussein (Al-Adab Journal, 2022)
Since "verb" is one of the most important grammatical categories and the center of gravity of the sentence, it was studied in this research based on the grammatical-stylistic analysis of verbs. Then applying this to selected poems of the poet "Jaleh Esfahani". This has been done according to the descriptive-analytical approach, and here, we shall point out the most important results that we have reached, which are: In terms of the “Pronoun”, we note the frequent usage of the “third person pronoun a lot” due to the expressive style used by “Jaleh Esfahani” in describing the past world and criticizing the state of her contemporary world. There is a close relationship between the poet and the subject of the poem. Also, we notice the frequent repetition of the predicate verb, and this indicates the poet's close connection to the event, and that most of the topics mentioned are nothing but personal experiences.